Dimensions of violence in Nursing: application of the questionnaire of negative acts (Research, Society and Development, 2021)
This study aims to identify the dimensions of work violence in the Nursing team related to negative acts. This is a quantitative, exploratory, cross-sectional study. With an estimated sample of 13,011 Nursing professionals, a revised negative acts questionnaire was used. The outcome variable was the questionnaire score, which allowed the evaluation of violence in four dimensions. For the data analysis, a descriptive analysis by means, standard deviations, minimum and maximum values of the scores of the continuous variables and proportions for the qualitative variables was used. The participation rate was 16.4%, corresponding to 2,136 professionals. Personal and professional disqualification was the dimension with the highest average score followed, respectively, by work-related harassment, personal harassment, and physical intimidation. From the identification and scoring of the negative acts referenced in the instrument applied, it was possible to identify the dimensions of violence in the daily lives of nursing professionals.